Use of Anxiolytics during Professional Examinations among Medical and Allied Students of Azra Naheed Medical College, Lahore - Muhammad Zahid, Muhammad Zahid Latif, Muhammad Atif Qureshi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anxiety is a common problem in our society. It assumes a special challenge when incidence of anxiety is high in medical students as compared to general population. This study was aimed to evaluate factors causing anxiety and the use of anxiolytics by medical& allied students prior to or during professional examinations. Methods: A cross sectional study was conducted from May 2022 to September 2022 in Azra Naheed Medical College among 3rd year MBBS & Allied health sciences students. A predesigned questionnaires were distributed among students through google forms recruiting 144 male/female students. A questionnaire was comprising of questions related to the use of anxiolytics, their reasons and how to cope up anxiety in future.The data of the students was finally entered for analysis. Results: Out of 144 students, 79(55%) were female respondents whereas 65(45%) were males. When asked about the use of anxiolytics,124(86%) students responded that they never used anxiolytics, only 5(3%) students admitted that they are in the habit of using anxiolytics. 109(74%) students found to be on anxiolytics to overcome stress. 12(8%) students experienced increase in the concentration in their studies after using anxiolytics. 19(14%) students experienced undesired effects. Only 9(6%) male students committed that anxiolytics helped in scoring good grade during examinations due to increase in concentration. Majority of the students i.e., 94(65%) agreed/strongly agreed to discourage the use of anxiolytics. In future, the students committed to adopt different methods instead of using anxiolytics to cope up stressful conditions. Conclusion: It is concluded that psychological screening of the students should be done at the time of induction in medical colleges. During their study, counselling system should be established which may be helpful for reduction of stress and anxiety. Key words: Anxiety, Social apprehension, Cognitive behavioral therapy